Upaya Kedutaan Besar Republik Indonesia Kuala Lumpur Dalam Meningkatkan Akses Pendidikan Dasar Anak Pekerja Migran Indonesia Melalui Program Sanggar Bimbingan - Nurrahman, Diyat; Triwahyuni, Dewi (Universitas Komputer Indonesia, 2024)
This study aims to analyze the efforts of the Embassy of the Republic of Indonesia Kuala Lumpur in Improving Access to Basic Education for Children of Indonesia Migrant Workers through the Sanggar Bimbingan Program. In this study, the researcher tries to analyze what efforts are made by the Embassy of the Republic of Indonesia Kuala Lumpur in improving access to education for children of Indonesia migrant workers and the results of these activities for the national interest of Indonesia. The research method used in this study is a qualitative method. In collecting the data, the researcher conducted literature studies, online searches, field observations, and interviews. As for the analysis technique, the researcher uses data redaction techniques. The results of this study explain that the Embassy of the Republic of Indonesia in improving access to basic education for children of Indonesia migrant workers through the Guidance Studio Program, will provide good benefits and results for the national interests of Indonesia, and the Indonesian government can also carry out obligations in the law for the fulfillment of children's rights, especially in the area of education. Keywords— Migrant, Diplomacy, Indonesia, Malaysia, Sanggar Bimbingan